GROWTH PERFORMANCE, CARCASS CHARACTERISTICS AND COST OF GAIN OF AWASSI AND KARADI LAMBS SLAUGHTERED AT DIFFERENT WEIGHT - KHALAF , FATAH M.; ORAY, KHALIL A. D. (Journal of Duhok University, 2021)
The study was carried out to investigate the effect of slaughter weights on growth performance, carcass characteristics and cost of gain of Awassi and Karadi ram lambs. Fifteen male lambs from either Karadi or Awassi were randomly blocked by live weight into three different slaughter weight groups (30, 40 and 50kg). Each lamb was kept in individual pen and offered an iso energetic and iso nitrogenous concentrate diet ad libitum. Lambs were slaughtered once they reached a target weight. Results reported the weight at slaughter increased for both breeds, there were significant reductions in average daily gain, bone percent, lean: fat ratio and increase in rib eye area, feed conversion ratio, fat tail weight and fat thickness. Moreover, Awassi lambs had a higher (p<0.01) dressing percentage 1 (49.41±0.32vs.47.69±0.66%) and 2 (58.32±0.45 vs. 56.06±0.51%), fat thickness (3.10±0.24 vs. 2.46±0.15mm) and loin percentage (8.74±0.11 vs. 8.11±0.07%) than Karadi lambs. In contrast, Karadi lambs had a higher (p<0.01) proportion of bone and lean: fat ratio and lower (p<0.01) proportion of fat than Awassi lambs. There was no significant differences in daily weight gains, rib eye area, the empty body weight, fat tail weight and shrinkage percent between breeds. In conclusion, the optimal slaughter weight is 40kg for both Awassi and Karadi lambs and cost of gain of Awassi lambs was lower than Karadi lambs and from economic trends lambs slaughtered at 30kg had higher profit potential